Dendrimer nanohybrid carrier systems: an expanding horizon for targeted drug and gene delivery. Issue 2 (February 2018) - Kesharwani, Prashant; Gothwal, Avinash; Iyer, Arun K.; Jain, Keerti; Chourasia, Manish K.; Gupta, Umesh
Highlights: Dendrimer-based hybrid systems are an emerging platform in the field of drug delivery. Hybrid nanomaterials are an important strategy in the field of nanomedicine. Hybrids could be used as a novel drug delivery system for several biomedical applications. Abstract : Highly controllable dendritic structural design means dendrimers are a leading carrier in drug delivery applications. Dendrimer- and other nanocarrier-based hybrid systems are an emerging platform in the field of drug delivery. This review is a compilation of increasing reports of dendrimer interactions, such as dendrimer–liposome, dendrimer–carbon-nanotube, among others, known as hybrid carriers. This should prompt entirely new research with promising results for these hybrid carriers. It is assumed that such emerging hybrid nanosystems – from combining two already-established drug delivery platforms – could lead the way for the development of newer delivery systems with multiple applicability for latent theranostic applications in the future. Teaser: Dendrimer hybrid carriers paving the way for the future design of a highly effective multifunctional drug delivery system.